2018
DOI: 10.18632/oncotarget.25020
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of bone marrow derived multipotent mesenchymal stromal cells for the treatment of steroid-refractory acute graft-versus-host disease: a multicenter prospective study

Abstract: The prognosis of steroid-refractory acute graft-versus-host disease (aGVHD) remains poor and better treatments are urgently needed. Multipotent mesenchymal stromal cell (MSC)-based therapy emerged as a promising approach but response rates were highly variable across studies. We conducted a multicenter prospective study assessing the efficacy of 1–2 infusion(s) of cryopreserved, third-party donor bone marrow-derived MSCs for treating grade II-IV steroid-refractory or -dependent aGVHD in a series of 33 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…However, the obtainment of any kind of response (either PR or CR) was sufficient to affect OS. This is consistent with previous studies in patients who, like ours, were refractory to several lines of treatment (Resnick et al, 2013;Kurtzberg et al, 2014;von Dalowski et al, 2016;Muroi et al, 2016;Dotoli et al, 2017;Servais et al, 2018). In contrast, other groups have reported that, when MSCs were administered soon after steroids, only CR are associated with improved OS (Le Blanc et al, 2008;Kebriaei et al, 2009;S anchez-Guijo et al, 2014).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…However, the obtainment of any kind of response (either PR or CR) was sufficient to affect OS. This is consistent with previous studies in patients who, like ours, were refractory to several lines of treatment (Resnick et al, 2013;Kurtzberg et al, 2014;von Dalowski et al, 2016;Muroi et al, 2016;Dotoli et al, 2017;Servais et al, 2018). In contrast, other groups have reported that, when MSCs were administered soon after steroids, only CR are associated with improved OS (Le Blanc et al, 2008;Kebriaei et al, 2009;S anchez-Guijo et al, 2014).…”
supporting
confidence: 94%
“…This observation is in contrast with other reports (Ball et al, 2013;von Dalowski et al, 2016) but the discrepancy could be ascribed to the fact that, in those studies, the dose ranges were too narrow and the number of patients too small to identify any correlation between response and dose. Our data have been confirmed by a recent multicentre prospective study, in which patients who received doses of 3-4x10 6 /kg body-weight had better responses and longer survival rates than those who received 1-2 9 10 6 /kg bodyweight (Servais et al, 2018). Our study confirms that patient age and the affected organ significantly affect responses to MSCs (Resnick et al, 2013;S anchez-Guijo et al, 2014).…”
supporting
confidence: 86%
“…Furthermore, an important consequence of these observations is that, although MSCs remain the necessary starting point for therapeutic immunosuppression, patient-derived cells play a crucial role in delivering such an immunosuppression. This new perspective, in line with clinical data whereby MSCs from the same donor can give different responses in different patients ( 72 74 , 76 , 78 , 79 , 150 ), may significantly affect the Research and Development sector of MSC manufacturing. In the last decades, much efforts have been spent on the identification of the most clinically effective MSC preparations.…”
Section: Role Of Mscs Undergoing Apoptosis To Deliver Immunosuppressimentioning
confidence: 63%
“…Albeit not strikingly biomarkers by definition, there have been several associative factors which can seemingly influence MSC responses among aGvHD patients. Dosage of MSC infusion, age of MSC recipients and organ involvement have been reported as affecting responses in aGvHD patients (72,77,78,82,84,85,130). Briefly, patients who received higher MSC doses (78,85), younger patients (72,82,84,85), or patients with gut or/and skin involvement seem to achieve a better response to MSCs (77,85,130).…”
Section: Msc Biomarkers For Gvhd: An Unmet Needmentioning
confidence: 99%
See 1 more Smart Citation